Nutritional status and immune response in murine experimental Jorge Lobo's disease - Barbosa, Adriana Sierra Assencio Almeida; Diório, Suzana Madeira; Pedrini, Silvia Cristina Barboza; Silva, Sônia Maria Uso Ruiz; Sartori, Beatriz Gomes Carreira; Calvi, Sueli Aparecida [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; Vilani-Moreno, Fátima Regina (Blackwell Verlag GmbH, 2015)
There are no studies investigating the role of nutritional status and immunity associated with Jorge Lobo's disease. The objective of this study was to evaluate the effects of protein-calorie malnutrition on the immune response of BALB/c mice inoculated with Lacazia loboi. In this study,the animals were divided into four groups: G1: inoculated with restricted diet, G2: not inoculated with restricted diet, G3: inoculated with regular diet, G4: not inoculated with regular diet. The animals of groups G1 and G2 were submitted to malnutrition for 20 days and once installed the animals were inoculated intradermally into the footpad. After 4 months, they were euthanised for the isolation of peritoneal lavage cells and removal of the footpad. The production of IL-2, IL-4, IL-10, IL-12, IFN-γ, TNF-α, H2 O2 and nitric oxide (NO) was evaluated in the peritoneal lavage cells. The footpad was evaluated regarding the size of macroscopic lesions, number of fungi and viability index. The results showed that the infection did not exert great influence on the body weight of the mice and previous malnutrition was an unfavourable factor for viability index, number of fungi, macroscopic lesion size in the footpad and production of H2 O2 , NO, IL-12, IL-10 and IFN-γ, suggesting that malnutrition significantly altered fungal activity and peritoneal cells. The results suggest considerable interaction between nutrition and immunity in Jorge Lobo's disease.
Keywords: Jorge lobo′s disease; Lacazia loboi; Immune response; Malnutrition; Mice